Caffeine-augmented Sprint interval training outcomes in obese women: an examination by inter-individual analysis on physical and physiological adaptive responses - Zhao, Xinying; Liu, Yang (Frontiers in Nutrition, 2025)
BackgroundThe objective of the present study was to elucidate the impact of a 12-week caffeine consumption before sprint interval training on the physical and physiological adaptations in obese women.MethodsThirty overweight and obese women volunteered and were randomly divided into three groups: Caffeine (3 mg·kg−1 body mass, n = 10), Placebo (3 mg·kg−1 body mass in cellulose, n = 10), and Control (n = 10). Over 12 weeks, subjects in the Caffeine and Placebo groups consumed their supplements three times per week, ~60 min before each sprint interval training session. Fat mass, lower body strength, and cardiorespiratory fitness were evaluated at baseline and after the intervention. Fasting glucose, lipid profiles, and adipokines (leptin, adiponectin, and irisin) were measured 48 h before and after the intervention.ResultsBoth the Caffeine and Placebo groups exhibited significant improvements (p < 0.05) in these variables after 12 weeks of training. The Caffeine group showed significantly greater adaptive responses (p < 0.05) than the Placebo group in reducing fat mass (SMD = −0.27), enhancing strength (SMD = 0.30) and cardiorespiratory fitness (SMD = 0.43), and altering fasting glucose (SMD = −0.74), leptin (SMD = −0.23), adiponectin (SMD = 0.18), and irisin (SMD = 0.42) after the intervention.ConclusionSupplementation of 3 mg·kg −1 body mass caffeine before sprint interval training resulted in greater reductions in fat mass and improvements in strength and cardiorespiratory fitness, as well as more pronounced changes in fasting glucose and adipokines among overweight and obese women.